2010
DOI: 10.1021/ml900028r
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of GSK2126458, a Highly Potent Inhibitor of PI3K and the Mammalian Target of Rapamycin

Abstract: Phosphoinositide 3-kinase R (PI3KR) is a critical regulator of cell growth and transformation, and its signaling pathway is the most commonly mutated pathway in human cancers. The mammalian target of rapamycin (mTOR), a class IV PI3K protein kinase, is also a central regulator of cell growth, and mTOR inhibitors are believed to augment the antiproliferative efficacy of PI3K/AKT pathway inhibition. 2,4-Difluoro-N-{2-(methyloxy)-5-[4-(4-pyridazinyl)-6-quinolinyl]-3-pyridinyl}benzenesulfonamide (GSK2126458, 1) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
234
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(244 citation statements)
references
References 25 publications
10
234
0
Order By: Relevance
“…[3][4] Recently, substituted-TZDs have been reported as PIM-2 enzyme inhibitors which have perspectives in the management of mutant cancer forms. 5 In various literature, 5-arylidene-thiazolidine-2,4-dione derivatives consisting of substituents at para or meta position of the benzylidene moiety have been identified to produce anticancer activity.…”
Section: Gsk1059615 and Its Analogs Are Pi3kαmentioning
confidence: 99%
“…[3][4] Recently, substituted-TZDs have been reported as PIM-2 enzyme inhibitors which have perspectives in the management of mutant cancer forms. 5 In various literature, 5-arylidene-thiazolidine-2,4-dione derivatives consisting of substituents at para or meta position of the benzylidene moiety have been identified to produce anticancer activity.…”
Section: Gsk1059615 and Its Analogs Are Pi3kαmentioning
confidence: 99%
“…15,16 In the current issue of Cancer Biology & Therapy, 17 Leung and colleagues used cell models of AE resistance derived from the hormone-responsive breast cancer line, MCF-7 to explore the cellular effects of two dual PI3K/mTOR inhibitors-NVP-BEZ235 (BEZ235) 18 and GSK2126458 (GSK212). 19 The authors had previously developed cellular models of resistance to TAM and AIs by prolonged culturing of MCF-7 cells in increasing concentrations of TAM or in the absence of estrogen, respectively. 20 Interestingly, while the resultant sub-lines displayed some phenotypic heterogeneity, all were resistant to TAM irrespective of how they were derived, 20 suggesting that broad resistance to TAM and AIs may develop via the dysregulation of common, upstream signaling pathways.…”
Section: Overcoming Resistancementioning
confidence: 99%
“…20 Leung and colleagues extended this work in their more recent study to determine the effect of AE resistance on the cellular response to the PI3K/mTOR inhibitors, BEZ235 and GSK212. 17 Both of these compounds are highly specific and potent small molecule inhibitors with efficacy against both class I PI3K isoforms and mTOR kinase activity, 18,19 that are currently being evaluated in phase I/II clinical trials either in breast cancer patients with advanced disease (BEZ235), or solid tumors and lymphomas (GSK212). The MCF-7 cell line is an appropriate preclinical model to examine the efficacy of these agents as not only is it an established and well characterized model of ER-positive, luminal breast cancer, but it also harbors a mutation in the helical domain of PI3KCA, 21 which encodes the catalytic (p110a) subunit of P13K.…”
Section: Overcoming Resistancementioning
confidence: 99%
“…At the same times, some literature have reported that the thienopyrimidine core can be used in preparing potent P2Y12 inhibitors [6]. For example, GDC-0941 and BKM 120 are a selective PI3K inhibitors which have been advanced into clinical evaluation [7][8][9][10]. At the same times, some literature point out 2-substituted thienopirimidin-4-one derivatives may serve as novel spasmolytic agents to treat disorders of smooth muscle function, and those compounds have a common features that are thieno [2,3-d] pyrimidin [11], the structure of thieno [2,3-d]pyrimidin and target compound was shown in Fig.…”
Section: Introductionmentioning
confidence: 99%